Surface aging behaviour of Fe-based amorphous alloys as catalysts during heterogeneous photo Fenton-like process for water treatment - Jia, Z.; Kang, J.; Zhang, W.; Wang, W.; Yang, C.; Sun, Hongqi; Habibi, D.; Zhang, L. (Elsevier BV, 2017)
Two novel, multifunctional Fe-based amorphous alloys with the nominal components of Fe78Si9B13 and Fe73.5Si13.5B9Cu1Nb3 exhibit advanced catalytic capability when degrading methyl blue (MB) and methyl orange (MO) dyes. The production rate of hydroxyl radicals ([rad]OH) in this work is 5–10 times faster than other Fe-based catalysts. The surface aging behaviour on Fe78Si9B13 and Fe73.5Si13.5B9Cu1Nb3 ribbons shows a significant effect on the dye degradation efficiency and reusability of the catalyst. Results reveal that crystallized a-Fe, iron oxide and SiO2 are gradually precipitated on the surface of the reused Fe78Si9B13 ribbon which ultimately becomes corroded through with holes. However, the inclusion of Nb atoms in the Fe73.5Si13.5B9Cu1Nb3 alloy causes the formation of niobium oxides which overlay the ribbon surface, and tend to reduce the contact area between the Fe and H2O2, thereby decreasing the generation of [rad]OH and further reducing the dye degradation efficiency. Tert-butanol is employed for quenching hydroxyl radicals ([rad]OH), causing a dramatic reduction in the amount available for degrading the MB and MO molecules. The MB and MO dye degradation and mineralization under UV–vis light are also fully investigated. The findings of this critically important work should form the basis of new research opportunities into the study of amorphous alloy catalysis.